Unpacking the black box between market culture and innovation performance: the role of absorptive capacity and resistance to change - Kara, Gizem; Turkcan, Hulya; Imamoglu, Salih Zeki; Ince, Huseyin (Emerald Group Publishing Ltd, 2024)
PurposeThis study aims to investigate the relationship between market culture and innovation performance and to reveal the role of absorptive capacity and resistance to change by building on the resource-based view.Design/methodology/approachData was gathered from 222 firm managers of manufacturing firms by using the survey method. Structural equation modeling and PROCESS macro were used to analyze the data.FindingsThe results indicate that market culture is positively related to innovation performance and absorptive capacity mediates this relationship. It is also found that resistance to change negatively moderates the relationship between market culture and innovation performance, but it has no moderating effect on the relationship between absorptive capacity and innovation performance.Originality/valuePrevious research examining the association between market culture and innovation performance is scarce and provides contradictory findings. This indicates that there is an underlying mechanism of this association neglected before. This study is an attempt to reconcile contradictory findings and enlighten the fuzzy areas of this relationship. Accordingly, this study focuses on absorptive capacity as a mediator and proves its role empirically. Moreover, this study is the first to examine the role of resistance to change and demonstrates its buffer role in the market culture-innovation performance link. It is also revealed that resistance to change does not moderate the relationship between absorptive capacity and innovation performance. The findings elucidate the underlying mechanism of the relationship between market culture and innovation performance, reconcile contradictory findings of extant research, expand the current knowledge, and provide practical implications.
Keywords: Market culture; Innovation performance; Absorptive capacity; Resistance to change